Vitamin D deficiency at the time of delivery - Prevalence and risk of postpartum infections. - Daniel Axelsson; Jan Brynhildsen; Marie Blomberg (PLoS ONE)
Background Postpartum infections are a common cause of morbidity after childbirth. Vitamin D deficiency has been shown to increase the risk for several infections in a non-pregnant population. Vitamin D deficiency has been described as common in pregnant women. Objective To investigate whether vitamin D deficiency in pregnant women in labor was associated with an increased risk of overall postpartum infectious morbidity within eight weeks of delivery. A secondary aim was to estimate the prevalence of vitamin D deficiency among pregnant women in Linköping, Sweden at the time of delivery. Material and methods Serum vitamin D levels in labor were analyzed for 1397 women. Vitamin D deficiency was defined as serum levels <50 nmol/L. All ICD-10 codes given to the women eight weeks postpartum were reviewed and postpartum infections were defined as the presence of an ICD-10 code suggestive of infection. The prevalence of postpartum infections among women with sufficient vitamin D levels was compared with women with vitamin D deficiency. Adjusted Odds Ratios and 95% confidence intervals for postpartum infections were calculated using multivariate logistic regression analysis. Results Fifty eight per cent of the women had serum vitamin D levels <50 nmol/L. The proportion of women with vitamin D deficiency varied, as expected, with season. No association between vitamin D deficiency and postpartum infections was found. For vitamin D 25-50 nmol/L the adjusted Odds Ratio was 0.85 (95% confidence interval 0.56-1.29) and for vitamin D <25 nmol/L the adjusted Odds Ratio was 1.15 (95% confidence interval 0.66-2.03). Women who smoked or who had a cesarean section had an increased risk of postpartum infections. Conclusions Vitamin D deficiency was more common than previously reported in Swedish pregnant women. No association between vitamin D deficiency and postpartum infections was found. Other well-known risk factors for postpartum infection were identified.